Metoprolol and Its Degradation and Transformation Products Using AOPs—Assessment of Aquatic Ecotoxicity Using QSAR - Voigt, Melanie; Bartels, Indra; Schmiemann, Dorothee; Votel, Lars; Hoffmann-Jacobsen, Kerstin; Jaeger, Martin (Molecules (Basel, Switzerland), 2021)
Pharmaceuticals are found in waterbodies worldwide. Conventional sewage treatment plants are often not able to eliminate these micropollutants. Hence, Advanced Oxidation Processes (AOPs) have been heavily investigated. Here, metoprolol is exposed to UV irradiation, hydrogen peroxide, and ozonation. Degradation was analyzed using chemical kinetics both for initial and secondary products. Photo-induced irradiation enhanced by hydrogen peroxide addition accelerated degradation more than ozonation, leading to complete elimination. Degradation and transformation products were identified by high-performance liquid-chromatography coupled to high-resolution higher-order mass spectrometry. The proposed structures allowed to apply Quantitative Structure-Activity Relationship (QSAR) analysis to predict ecotoxicity. Degradation products were generally associated with a lower ecotoxicological hazard to the aquatic environment according to OECD QSAR toolbox and VEGA. Comparison of potential structural isomers suggested forecasts may become more reliable with larger databases in the future.